Sistem Informasi Pangan Dan Gizi Berbasis Web Pada Dinas Ketahanan Pangan Kabupaten Garut - Syahril, Ari Amirul; Suharto, Edi (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The Garut Regency Food Security Service is in charge of evaluating and reporting on food availability or insecurity, distribution, food reserves, consumption, food diversification and food security in Garut Regency, including overcoming food insecurity and community nutrition. In carrying out its duties of delivering information to the public using a WEB-based information system, namely the FOOD SECURITY AND NUTRITION SYSTEM (SKPG), but this system can only convey general information regarding official profiles, activities, news articles, announcements. There are no system features available for managing rice price data, community nutrition data, planting area data and harvest failure data in Garut district that can be done by the department.With the limited features contained in this system, it makes it difficult for the department to manage data and information. So as a solution this research aims to develop a web-based information system with data and information management features from the user side, namely the operator and the community. This study aims to build a web-based information system so that the Garut Regency Food Security Service can help the community and government ranks to provide information and obtain activity data, potential and advantages including rice price data, community nutrition data, planting area data and harvest failure data in Garut Regency. , which can be accessed easily and quickly by the public. The web-based information system is designed using UML, with the implementation using the PHP Native programming language, HTML and MySQL database, as well as the Waterfall system development process model.